Factors affecting length of hospital stay in stroke survivors in South Africa: A call for a stroke unit - Stephanie C. Pillay; Roxann Redant; Nadia Umuneza; Azra Hoosen; Fiona Breytenbach; Sameera Haffejee; Zvifadzo Matsena-Zingoni; Kganetso Sekome (African Journal of Disability, 2022)
Background: Stroke in Africa is a growing and neglected crisis with the incidence more than doubling in low- to middle-income countries in the last four decades. Despite this growing threat, implementation of stroke models of care in hospitals is lacking. Stroke units as a model of care have been shown to decrease mortality, reduce length of hospital stay (LOS) and improve outcomes in stroke survivors.